METHODOLOGICAL APPROACHES TO THE FORMATION AND IMPLEMENTATION OF AN INVESTMENT AND INNOVATION STRATEGY FOR PHARMACEUTICAL ENTERPRISES - PROKOPENKO, Nataliya; BYSHOVETS, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the formation of mechanisms for managing the innovative development of pharmaceutical enterprises, which is a complex and multifaceted process that takes into account the specific features of this industry, high dependence on scientific research, a strict regulatory environment and the strategic importance of innovation for competitiveness. In today’s environment, pharmaceutical companies face ever-increasing demands on product quality, drug safety, shorter drug development cycles and adaptation to global challenges such as pandemics, population ageing or new chronic diseases. All this determines the need to create an effective mechanism for managing innovation development, which would ensure not only high productivity indicators, but also the social significance of the industry. It is established that the pharmaceutical industry is one of the most innovation-intensive sectors of the economy. By its very nature, it depends on a systematic approach to innovation management, since the creation of new medicines requires long-term scientific research, a large amount of financial resources and the integration of modern technologies. In this context, the mechanism for managing innovation development should cover all stages of the innovation life cycle, from basic research to commercialisation and product launch. An important component is the research and development (R&D) process, which forms the basis of the industry’s innovation potential. The article identifies and describes the dependence of the mechanism of innovation management in the pharmaceutical sector on the regulatory environment. At each stage - from drug development to its introduction into production and sale - companies must comply with strict regulations, such as GMP (Good Manufacturing Practices), GLP (Good Laboratory Practices) and GCP (Good Clinical Practices). This complicates innovation management, as it is necessary to take into account not only technological aspects, but also safety, efficiency and compliance with the legal norms of different countries. The author argues that the financial aspect plays a key role in the mechanism of managing the innovative development of pharmaceutical enterprises. The development of a new medicinal product may require many years of investment in research and clinical trials. For example, researchers estimate that the average cost of developing a new drug can reach several billion dollars. Therefore, an important element of the mechanism is to ensure access to funding, both internal and external, in particular through cooperation with venture capital funds, grants or partnerships with other companies. A classification of components of innovation development management in the pharmaceutical sector as a high-tech industry is developed. It is proved that the formation of a mechanism for managing innovative development in pharmaceuticals requires consideration of many factors, including strategic planning, multichannel financing, compliance with regulations, development of scientific research and integration of the latest technologies. This mechanism should ensure synergy between all elements of the innovation process, contributing to the creation of products that not only meet high standards, but also ensure accessibility and high social value for society. Thus, effective management of innovation development in the pharmaceutical industry is the key not only to the economic success of enterprises, but also to improving the quality of life on a global scale.